2008
DOI: 10.1161/circulationaha.107.736785
|View full text |Cite
|
Sign up to set email alerts
|

Does Size Matter?

Abstract: Abstract-Extensive evidence is available that cardiovascular structure and function, along with other biological properties that span the range of organism size and speciation, scale with body size. Although appreciation of such factors is commonplace in pediatrics, cardiovascular measurements in the adult population, with similarly wide variation in body size, are rarely corrected for body size. The patient is a very tall 23-yearold competitive rower with a height of 203 cm and weight of 100 kg referred to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
125
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(135 citation statements)
references
References 64 publications
10
125
0
Order By: Relevance
“…and Bella et al [16][17][18] We also verified that in our study population, the allometric coefficients used were body size independent (BSI); to be considered BSI, no relationship should be observed between the scaled parameter and the scaling parameter. For BSA or height, we used the allometric coefficients recommend by the ASE guidelines.…”
Section: Methodssupporting
confidence: 84%
See 1 more Smart Citation
“…and Bella et al [16][17][18] We also verified that in our study population, the allometric coefficients used were body size independent (BSI); to be considered BSI, no relationship should be observed between the scaled parameter and the scaling parameter. For BSA or height, we used the allometric coefficients recommend by the ASE guidelines.…”
Section: Methodssupporting
confidence: 84%
“…15 Scaling of cardiac dimensions, volumetric and mass data to LBM was performed using allometric coefficients. The choices of coefficients were based on the literature especially the studies of George et aland Bella et al [16][17][18] We also verified that in our study population, the allometric coefficients used were body size independent (BSI); to be considered BSI, no relationship should be observed between the scaled parameter and the scaling parameter. For BSA or height, we used the allometric coefficients recommend by the ASE guidelines.…”
supporting
confidence: 71%
“…43 Indexing to a power of height is the most widely accepted method of indexation in older children, but it is less consistently applied in adults. Of people with hypertension, LVH may be underdiagnosed in those that are obese, where measured mass may be elevated; however, it is incorrectly compensated for by adjusting for BSA.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been shown that indexation to height 2.7 provides the highest prevalence of LVH, to some extent independently from the cut-off settled, since this normalization identifies both obesity-and BP-related LVH. 22 In the VITAE Study (Ventriculo Izquierdo Tension Arterial Espana) including 946 essential hypertensives (53.3% women, 45% obese) from primary care centres, LVH prevalence ranged from 59.2% by indexing to BSA (that is, LVMI X111/102 g m À2 ) to 70.7% by indexing to height (that is, LVMI X50/ 47 g m À2.7 ). 23 In the Gubbio Population Study, a clinical survey performed in a small Italian town, the prevalence of LVH among 250 hypertensive patients was nearly twofold higher (43.6 vs 24.0%) when LVM was indexed to height (that is, LVMI 49.2/46.7 g m À2.7 ) compared to BSA indexation (that is, 116/104 g m À2 ).…”
Section: Discussionmentioning
confidence: 99%